2023
DOI: 10.20945/2359-3997000000585
|View full text |Cite
|
Sign up to set email alerts
|

Very low HDL levels: clinical assessment and management

Abstract: In individuals with very low high-density lipoprotein (HDL-C) cholesterol, such as Tangier disease, LCAT deficiency, and familial hypoalphalipoproteinemia, there is an increased risk of premature atherosclerosis. However, analyzes based on comparisons of populations with small variations in HDL-C mediated by polygenic alterations do not confirm these findings, suggesting that there is an indirect association or heterogeneity in the pathophysiological mechanisms related to the reduction of HDL-C. Trials that ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 149 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…Besides ApoA-I, other HDL components, such as HDL-associated hydrolases (e.g., paraoxonase-1), certain (lyso)phospholipids, nutrition, smoking, air pollution, and plastic-associated chemicals influence HDL’s functionality ( 38 ). In individuals with very low HDL-C, due to rare monogenic dyslipidemia (e.g., Tangier disease, LCAT deficiency, familial hypoalphalipoproteinemia) or due to secondary dyslipidemias, the very low HDL-C levels are associated with (1) increased risk of CVD, (2) comorbidities, such as T2DM, and (3) elevated levels of sdLDL ( 39 ).…”
Section: Residual Risk Factorsmentioning
confidence: 99%
“…Besides ApoA-I, other HDL components, such as HDL-associated hydrolases (e.g., paraoxonase-1), certain (lyso)phospholipids, nutrition, smoking, air pollution, and plastic-associated chemicals influence HDL’s functionality ( 38 ). In individuals with very low HDL-C, due to rare monogenic dyslipidemia (e.g., Tangier disease, LCAT deficiency, familial hypoalphalipoproteinemia) or due to secondary dyslipidemias, the very low HDL-C levels are associated with (1) increased risk of CVD, (2) comorbidities, such as T2DM, and (3) elevated levels of sdLDL ( 39 ).…”
Section: Residual Risk Factorsmentioning
confidence: 99%
“…Our study findings couldn't establish a positive correlation of TAGs with that of gene expression in deranged lipid and diabetic subjects while a significant difference was observed in levels of triglycerides with that of diabetics in a study 33 . The prevalence of dyslipidemia has been observed to be increased in 60-70% patients of type www.nature.com/scientificreports/ II diabetes mellitus, being low HDL level dominant in worsening the glucose tolerance among diabetics 34,35 . A study conducted on Pakistani population reported that lipid parameters are alarmingly high in type 2 diabetes mellitus specially among the newly diagnosed ones 36 .…”
Section: Discussionmentioning
confidence: 99%
“…According to studies done on different populations, 18.7% of individuals with very low HDL‐C levels carry rare genetic variants of great effect and 19.3% carry common low‐effect variants 43 . Thus, the genetic basis of low HDL‐C levels is often regarded as polygenic 44 …”
Section: Causes Of Low Hdl‐c: Predisposing Factors For Diabetesmentioning
confidence: 99%